A Review on Digital Technology in the Business Field - Kishor Kumar Dash (AG Volumes, 2022)
The advent of digital technology has caused profound shifts in how we work, play, communicate, and even go about our daily lives. The implementation of digital transformation has the potential to increase profitability, accelerate the time it takes to bring goods to market, and convert consumer happiness into brand loyalty. The era of digital technology is the one in which we presently find ourselves. We've seen a wide range of amazing advancements over the course of so many years thanks to the relentless march of technological progress. For instance, we have progressed from using horse-drawn carriages to semi-automated autos, in addition to the myriad of other significant advancements that have substantially raised the bar for our levels of productivity, communication, and general quality of life. The world of business has also been profoundly influenced as a direct result of these events. The digital transformation has resulted in enhanced experiences for customers and employees alike, as well as in increased efficiency across a wide range of tasks.Businesses that operate in the digital space rely on technology to generate new forms of value in their business models, the experiences they provide for their customers, and the internal capabilities they use to support their primary business functions. This word refers to conventional players as well as digital-only firms that are undergoing a transformation of their operations thanks to the use of digital technology. The adoption of digital transformation strategies is essential for all sizes and types of organisations, from startups to multinational corporations. This is a point that is driven home in almost every keynote address, panel discussion, article, and research that addresses the topic of how organisations may stay competitive and relevant as the world gets more digital.